BREAKING THE GLASS CEILING THROUGH SOCIAL CAPITAL: UNDOCUMENTED STUDENTS AND THE QUEST FOR HIGHER EDUCATION - Greene, Patrick (East Carolina University, 2021)
Undocumented students attend public schools throughout the United States alongside citizen students. These undocumented students face the same requirements and expectations of all others in regard to achievement in schools, however those that dream of attending an institution of higher learning may be staring at that dream through a glass ceiling. Despite academic successes, undocumented students are limited or excluded from admission or funding for college due to their residency status. The pressures of trying to succeed in a system designed against them, leads many undocumented students to seek assistance from various persons in their family, school, and community. In this case study, the researcher examined the experiences of four undocumented Latinx students that graduated from the Greene County school system in Snow Hill, North Carolina and successfully attended some form of higher education. This study identifies the people and themes that were essential to their success and found themes of social capital available to these students locally and compared the experiences of those students to recommendations from national organizations. The study concluded that undocumented students looked to roles in their families for encouragement and emotional support while they looked to trusted school personnel for assistance in navigating their issues with application and funding for higher education. These students also completed the social capital theory by assisting other undocumented students as a source of knowledge. Using this information, a local plan was developed to aid future undocumented students seeking access to higher education.
Keywords: undocumented; immigration; K12 school; Children of illegal aliens--Education (Higher)--North Carolina--Snow Hill; Immigrant students--North Carolina--Snow Hill; Hispanic American students--Education (Higher)--North Carolina--Snow Hill; Social capital (Sociology)--North Carolina; Community and school--North Carolina